THE ACTION OF RENIN ON RABBITS WITH RENAL HYPERTENSION - Taggart, John (The Rockefeller University Press, 1940)
Our results lead us to believe that renin in the form in which it is extracted from the kidney cannot be the agent causing chronic renal hypertension. The reasons against accepting renin as the pressor substance responsible for the hypertension of renal ischemia may be summed up as follows:— 1. The high blood pressure levels of renal ischemia cannot be approximated by any constant injection of renin that will maintain a sustained increase in normal animals. 2. The ratio of size of response to size of dose becomes progressively less as the amount of the dose is increased. If the hypertension of renal ischemia were due to a large elaboration of renin in the body, a small dose injected would be expected to have much less effect than in a normal individual. This is not the case; the response of the hypertensive animal to a given dose of renin is the same. Also animals with increased blood pressure due to a constant infusion of renin respond differently qualitatively and quantitatively to renin than do animals hypertensive from renal ischemia. 3. Since renin exhibits the phenomenon of tachyphylaxis one cannot explain the sustained hypertension of renal ischemia as due to a substance toward which the body becomes refractory as more and more of it is given. If tolerance results from the presence in the renin preparation of an antagonistic contaminant which persists longer in the body than the pressor agent, renal hypertension is definitely not caused by renin. This follows from our observations that rabbits hypertensive from renal ischemia, and in which tolerance is produced, maintain the blood pressure they had before injection of any renin.